Wool trade, agrarian structure and oligarchy in southern Peru - Jacobsen, Nils (1982)
The economic development in the south of Peru towards the end of the 19th century and the beginning of the 20th century, a period in which the export of wool was of determining importance, represents a special problem for Peruvian history: Why? -In the cattle ranches and the indigenous communities-were the structures of agrarian production maintained so traditional and archaic, without capital investments, intensifying production methods or introducing salaried labor relations in the large agricultural estates?